THE EFFECT OF KNOWLEDGE CREATION ON BANK PERSONNEL PERFORMANCE - Ali Shayesteh & Hamidreza Yaghubi (International Journal of Research Science and Management, 2015)
Today, organizations try to find new tools as solutions in order to survive. Knowledge management is a solution, which can help organizations to achieve their aims. This solution can reform functional specifications for organizations via giving the ability of “more intelligent performance”. To do so, this research has reviewed the effect of knowledge creation on the performance of staffs working at Sarmaye Bank as one the financial firms in Tehran. This research is a kind of practical, descriptive and nonexperimental survey. The data gathered from research questionnaires. Richardson and Cronbach’s Alpha method used to validate the questionnaire. In addition, structural equation model with the help of AMOS software used to analyze the gathered data. The results showed that the process of knowledge creation has a positive and meaningful effect on staff performance.